Association between near occlusal contact areas and mixing ability. (25th August 2014) - Horie, T.; Kanazawa, M.; Komagamine, Y.; Hama, Y.; Minakuchi, S.
Summary This study investigated the relationship between occlusal contact and near contact areas defined by clenching intensity using electromyograms (EMGs) and mixing ability assessed with colour‐changeable chewing gum. Participants comprised 44 dentate adults (24 men, 20 women) with a mean age of 28·2 ± 6·8 years. Silicone material was used to measure the occlusal contact and near contact areas (the area of each type of tooth, the total area of the first molar and second molar, the second premolar to the second molar and the first premolar to the second molar) defined by clenching intensity at 10% maximum voluntary contraction (MVC). Colour‐changeable chewing gum was used to assess mixing ability. A colorimeter was used to measure colour changes, and the calculated colour difference (ΔE) was used as a measure of mixing ability. Correlation analysis of ΔE and occlusal contact and near contact areas revealed a significant positive correlation of 0·47 at 0–160 μm thicknesses of the silicone registration material of the second molar (P < 0·01). The near contact area with a thickness up to 200 μm was correlated with mixing ability, with the correlation strengthening as the interocclusal distance increased up to 160 μm. Notably, occlusal contact and near contact areas of the second molar were strongly correlated with mixing ability in dentate adults.